Processing of food products and wastes with high voltage electrical discharges - Vorobiev, Eugene; Boussetta, Nadia; Lebovka, N. I. (Nikolai Ivanovich) (Academic Press, 2023)
Processing of Food Products and Wastes with High Voltage Electrical Discharges presents basic knowledge on HVED technology, focusing on the mechanisms, related phenomena and effects, equipment design, methods and examples of application. Divided in three parts, the book covers the advantages and restrictions of HVED technology for the treatment of numerous specific food products, by-products and wastes, such as grape, oilseed, citrus by-products and wastes, lignocellulosic and algal biomass, meat and bacterias. This book act as a comprehensive resource for researchers to be able to use the data for the dimensioning of HVED and processing equipment and finding the optimal treatment parameters.